2017
DOI: 10.1101/185512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel data-driven model for real-time influenza forecasting

Abstract: Abstract-We provide data-driven machine learning methods that are capable of making real-time influenza forecasts that integrate the impacts of climatic factors and geographical proximity to achieve better forecasting performance. The key contributions of our approach are both applying deep learning methods and incorporation of environmental and spatio-temporal factors to improve the performance of the influenza forecasting models. We evaluate the method on Influenza Like Illness (ILI) counts and climatic data… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…For recent reviews of DNNs, see [3], [4]. DNNs have been remarkably successful in many applications including image recognition [1], [5], [6], object detection [7], [8], speech recognition [9], biomedicine and bioinformatics [10], [11], temporal data processing [12], and many other applications [4], [13], [14]. These recent advances in artificial intelligence (AI) have opened up new avenues for developing different engineering applications and understanding of how biological brains work [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…For recent reviews of DNNs, see [3], [4]. DNNs have been remarkably successful in many applications including image recognition [1], [5], [6], object detection [7], [8], speech recognition [9], biomedicine and bioinformatics [10], [11], temporal data processing [12], and many other applications [4], [13], [14]. These recent advances in artificial intelligence (AI) have opened up new avenues for developing different engineering applications and understanding of how biological brains work [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep learning based LSTM has garnered significant attention for time series forecasting of various trends. LSTM has been previously employed to forecast: weather [9] , stock price movements [10] [11] , pandemics [12] , solar irradiance [13] [14] , atmospheric pollution levels [15] . They have also been employed to predict the answers to questions [16] , predicting the next word [17] etc .…”
Section: Introductionmentioning
confidence: 99%
“… Results indicated that the RF model outperformed the SVM and MARS and it can be utilized to diagnose the behavior of brucellosis over time. Venna et al [97 ] Influenza ARIMA, EAKF, LSTM Propose a novel data-driven machine learning method using long short-term memory-based multi-stage for influenza forecasting. Proposed method performs better than the existing well-known influenza forecasting methods (ARIMA and EAKF) and the results offer a promising direction to improve influenza forecasting.…”
Section: Resultsmentioning
confidence: 99%